2016
DOI: 10.4103/0970-9185.194771
|View full text |Cite
|
Sign up to set email alerts
|

The effect of epidural dexmedetomidine on oxygenation and shunt fraction in patients undergoing thoracotomy and one lung ventilation: A randomized controlled study

Abstract: Background and Aims:Role of epidural dexmedetomidine in providing analgesia is well documented, but its effect on oxygenation and shunt fraction is not well established. We studied the hypothesis that epidural dexmedetomidine may improve oxygenation and shunt fraction during one-lung ventilation (OLV).Material and Methods:After taking Institutional Ethics Committee approval, sixty patients undergoing thoracotomy and OLV were randomized to receive epidural ropivacaine with saline (RS group) or epidural ropivaca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Meta-analysis of pH Seven trials including 345 patients reported pH (20,23,24,(26)(27)(28)(29). The pooled data showed no signi cant difference between the dexmedetomidine group and the placebo group (MD: 0.03; 95% CI: from 0.00 to 0.07, p=0.04).…”
Section: Results Of Meta-analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Meta-analysis of pH Seven trials including 345 patients reported pH (20,23,24,(26)(27)(28)(29). The pooled data showed no signi cant difference between the dexmedetomidine group and the placebo group (MD: 0.03; 95% CI: from 0.00 to 0.07, p=0.04).…”
Section: Results Of Meta-analysismentioning
confidence: 99%
“…After searching the database and comparing the present criteria, a total of 17 trials were included in the meta-analysis (16,19,20,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). These trials are all randomized control trials.…”
Section: Selection Of Trialsmentioning
confidence: 99%
See 2 more Smart Citations
“…It deserves mentioning that dexmedetomidine had been administered through epidural infusion in a dose of 0.2 µg/kg/h during the intraoperative period only, and they claimed that it improves oxygenation and reduces the shunt fraction during one lung ventilation. 28 …”
Section: Discussionmentioning
confidence: 99%